Classification of Ordered Type Soliton Metric Lie Algebras by a Computational Approach - Hülya Kadıoğlu (Abstract and Applied Analysis)
We classify some soliton nilpotent Lie algebras and possible candidates in dimensions 8 and 9 up toisomorphy.We focus on type of derivations, where is the dimension of the Lie algebras. We present algorithms to generate possible algebraic structures.